2014
DOI: 10.1016/j.jss.2014.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Dietary advanced glycation end-products, its pulmonary receptor, and high mobility group box 1 in aspiration lung injury

Abstract: Background Gastric aspiration is a significant cause of acute lung injury and acute respiratory distress syndrome. Environmental risk factors, such as a diet high in pro-inflammatory advanced glycation end-products (AGEs), may render some patients more susceptible to lung injury after aspiration. We hypothesized that high dietary AGEs increase its pulmonary receptor, RAGE, producing an amplified pulmonary inflammatory response in the presence of high mobility group box 1 (HMGB1), a RAGE ligand and an endogenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…HMGB1 is a highly conserved non-histone chromosome binding protein, which is closely related to a variety of lung diseases, including pneumonia (Tseng et al, 2014), tuberculosis (Zeng et al, 2015), chronic obstructive pulmonary disease (Sukkar et al, 2012), pulmonary fibrosis (Smit et al, 2014), and lung transplantation (Weber et al, 2014). Normally, HMGB1 is mainly concentrated in the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…HMGB1 is a highly conserved non-histone chromosome binding protein, which is closely related to a variety of lung diseases, including pneumonia (Tseng et al, 2014), tuberculosis (Zeng et al, 2015), chronic obstructive pulmonary disease (Sukkar et al, 2012), pulmonary fibrosis (Smit et al, 2014), and lung transplantation (Weber et al, 2014). Normally, HMGB1 is mainly concentrated in the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that increased production of proinflammatory cytokines and neutrophil accumulation could cause manifested inflammation, and Smit et al observed that upregulated HMGB1 induced these phenomena via activation of RAGE in aspiration lung injury [ 36 ]. Therefore, to assess whether XBJ treatment can reduce inflammatory cells counts and cytokines through reduced HMGB1 and RAGE expressions in the lung, differential cell counts and TNF- α , IL-1 β , and IL-6 levels were simultaneously investigated in the BAL fluids of the mice treated with or without XBJ at 6, 24, and 48 hours after CLP.…”
Section: Discussionmentioning
confidence: 99%
“…PF is a respiratory disease caused by the scars formed in the lung tissues, leading to serious breathing problems. HMGB1 levels were significantly elevated in BALs or sputum in patients with PF [88]. Elevated sputum HMGB1 was correlated to 10% increased risk of lung function decline, whereas the increase in serum HMGB1 was associated with 5% increased risk of pulmonary disease progression [103].…”
Section: Pulmonary Fibrosis (Pf)mentioning
confidence: 95%
“…In addition, red blood cell (RBC) transfusion could enhance the susceptibility to lung inflammation through released HMGB1 . Neutralizing anti‐HMGB1 monoclonal antibody conferred significant protection against PA‐induced neutrophil recruitment, bacterial infection and lung injury . In the presence of HMGB1, high dietary AGEs could increase RAGE expression to augment inflammatory response to aspiration .…”
Section: Hmgb1 In Lung Diseasesmentioning
confidence: 99%